The knowledge of family health team on the action of physical therapist in primary care - - Greicimar de Oliveira; Ercília de Souza Andrade; Marcelo Lasmar dos Santos; Gabrielle Silveira Rocha Matos (Universidade de Fortaleza, 2012)
Objective: To evaluate the knowledge of health team from Basic Health Units in the city of Coari-AM, Brazil, on the action of physical therapist in primary care. Methods: A quantitative, exploratory and descriptive study, like a field survey conducted in 11 primary care units in Coari, Amazonas state. The data were collected through a questionnaire comprising closed questions regarding the action of physical therapist in primary care. 76 professionals joined in the survey by category: (05) physicians, (10) nurses, (08) nursing technicians and (53) community health workers. Results: 61.64% (n = 45) of the professionals working in the family health team reported knowing the action of physical therapist in primary care; 79.45% (n = 58) referred it in secondary level and 69.86% (n = 51) at the tertiary level of health care. Conclusion: This work showed some knowledge of professionals on the professional action of physical therapists in primary care; however, the knowledge for this level presents itself disadvantaged in relation to other levels of health care. We demonstrated that a share of professionals presented difficulties to consider the possibility of physiotherapeutic intervention in diseases mostly worked in primary care, but the reference to the viability of action of physical therapist for different publics was satisfactory. This conclusion does not exhaust the possibility of discussing the proposed theme.